The Production of Ethanol from Sugar Beet Waste by Immobilized Saccharomyces Cerevisiae - Al-Hilo, Jasim; J. Mohammed, Thamir; A. Al-Naime, Rana (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Saccharomyces Cerevisiae cells were immobilized in calcium alginate beads and activated charcoal for use in the production of ethanol from batch fermentation of sugar beet waste. Treatment of the waste with NaOH to increase the ability of lignocellulose material to hydrolysis by acid (2N H2SO4) to monosaccharide and disaccharide (mainly glucos). The high reducing sugar concentration obtained was equal to 9.2gm/100ml (10Brix) after treatment. Fermentation parameters, are (pH, glucose concentration (2.5-25 gm/100ml), immobilized agent concentration (2.5-25 gm/100ml) were studied to find the optimum physiological condition. And the highest ethanol concentration obtained from the fermentation in the presence of 20%(wt/v) calcium alginate was (9.322%(wt/v)) at 13.75%(wt/v) glucose concentration and pH 5 .The experimental results were correlated by empirical second order polynomial equation with correlation coefficient 96.734% and variance 93.574%